The Effects of Running Ultramarathons on the Structures of the Knee: An MRI Study - Hagemann, Glen J.; Rijke, Arie M.; Corr, Peter D. (Current Overview on Disease and Health Research Vol. 1, 2022)
The objective of this study was to determine the effects of ultramarathon running on the structures of the normal knee and on any pre-existing abnormalities of the knee using magnetic resonance (MR)imaging. It was hypothesized that the race aggravates the overuse injuries specific to marathon running but does not affect the MR appearance of pre-existing or healed knee injuries. The knees of ten prospectively selected participants who completed a Comrades Marathon in the period between 1997 and 2002 were scanned using magnetic resonance imaging. Participants knees were scanned 48 hours prior to the race, 48 hours subsequent to the race and one month following the race. MR imaging scores of all knee injuries detected on the scans immediately prior to the race were compared with the scores after the race. It was found that all knees scanned demonstrated the presence of an abnormal amount of joint fluid before the race. This amount was found to be further increased immediately after the race in five runners and remained unchanged in the other five. Five runners had reduced joint fluid and five had remained unchanged one month later; however the runners in each of these five groups were not the same as those in the post-race groups. Four runners had increased signal intensity in the distal patellar and quadriceps tendons before the event, while six athletes had increased or kept the same on post-race scans. On scans conducted one month later, there was a drop in signal intensity in three runners, with complete resolution in two and no change in one runner. Old, healed injuries to ligaments, tendons or other knee structures were unaffected by the race. In conclusion, it appears that the event has a detrimental effect on those runners who start the ultramarathon with tendinopathy, which worsens by MRI criteria on the post-race scan. One month after the race, the scan appearance of the overuse injury had either improved or resolved completely. Bone bruising or meniscal damage does not appear to occur in the knees of runners as a result of competing in the Comrades Marathon.